Detection of the irradiated donor in the LMXBs 4U 1636-536 (=V801 Ara) and 4U 1735-444 (=V926 Sco) - Casares, J; Cornelisse, R; Steeghs, D; Charles, P; Hynes, R; O'Brien, K; Strohmayer, T (2006)
Phase-resolved VLT spectroscopy of the bursting low-mass X-ray binaries 4U 1636-536/V801 Ara and 4U 1735-444/V926 Sco is presented. Doppler images of the N III λ4640 Bowen transition reveal compact spots which we attribute to fluorescent emission from the donor star and enable us to define a new set of spectroscopic ephemerides. We measure K em = 277 ± 22 and 226 ± 22 kms -1 from the N III spots in V801 Ara and V926 Sco, respectively, which represent strict lower limits to the radial velocity semi-amplitude of the donor stars. Our new ephemerides provide confirmation that light-curve maxima in V801 Ara and likely V926 Sco occur at superior conjunction of the donor star and hence photometric modulation is caused by the visibility of the X-ray heated donor. The velocities of He II λ4686 and the broad Bowen blend are strongly modulated with the orbital period, with phasing supporting emission dominated by the disc bulge. In addition, a reanalysis of burst oscillations in V801 Ara, using our spectroscopic T 0, leads to K 1 = 90-113 kms -1. We also estimate the K-corrections for all possible disc flaring angles and present the first dynamical constraints on the masses of these X-ray bursters. These are K 2 = 360 ± 74 kms -1, f(M) = 0.76 ± 0.47 M ⊙ and q = 0.21-0.34 for V801 Ara and K 2 = 298 ± 83 kms -1, f(M) = 0.53 ± 0.44 M ⊙ and q = 0.05-0.41 for V926 Sco. Disc flaring angles α ≥ 12° and q ≃ 0.26-0.34 are favoured for V801 Ara whereas the lack of K 1 constraint for V926 Sco prevents tight constraints on this system. Although both binaries seem to have intermediate inclinations, the larger equivalent width of the narrow N III line in V801 Ara at phase 0.5 relative to phase 0 suggests that it has the higher inclination of the two. © 2006 RAS.